United States Food and Drug Administration's authorization of reduced exposure claims for IQOS®: implications for regulation in Latin America - Robert Eckford; Gianella Severini; Ernesto M. Sebrié; Monique E. Muggli; Alexandra Beem; Debra Rosen; Eric Crosbie (Pan American Health Organization, 2022)
Philip Morris International has used the July 7, 2020 United States Food and Drug Administration's (US FDA) modified risk tobacco product order for IQOS®, which authorized certain reduced exposure marketing claims, as a corporate strategy to promote and normalize its heated tobacco products in Latin America. The modified risk tobacco product orders are based on the US's unique regulatory system that is not, and should not be, replicated anywhere else in the world. Philip Morris International's global public relations campaign largely ignored the FDA's rejection of reduced risk claims for IQOS and other key FDA findings that are important for policy-makers, regulators, and consumers - including tobacco users and Philip Morris International's customers - to understand the risks associated with the product. In Latin America in particular, Philip Morris International has used media outlets to promote this misleading information to the public. This company has also used the FDA ruling to lobby regulators in Latin America to relax regulations on IQOS in the region. As tobacco companies rapidly introduce new tobacco products in low- and middle-income countries, public health advocates and Parties to the World Health Organization (WHO) Framework Convention on Tobacco Control (FCTC) should take measures to prevent the promotion of misleading statements about heated tobacco products, including IQOS. As Latin American countries are at different stages in their regulation of heated tobacco products, governments should adhere to their WHO FCTC obligations and the recommendations of the Conference of the Parties by entirely prohibiting the sale of heated tobacco products or strictly applying to heated tobacco products all the relevant tobacco demand-reduction policies based on the WHO FCTC (making sure to capture both heated cigarettes and heating devices).